A Ring Closing Metathesis Approach to the Formal Synthesis of (+)‐Callyspongiolide. Issue 22 (7th September 2020) - Ko, Kwang‐Yoon; Wilson, Zoe E.; Furkert, Daniel P.; Brimble, Margaret A.
Abstract: An enantioselective synthesis of macrocyclic core of (+)‐callyspongiolide is described, constituting a formal synthesis of this natural product. The synthetic strategy constructs the 14‐membered macrocyclic domain via Yamaguchi esterification followed by a challenging ring‐closing metathesis (RCM) to effect the final formation of the macrolactone. Abstract : A challenging cyclisation : An enantioselective synthesis of macrocyclic core of (+)‐callyspongiolide is described, constituting a formal synthesis of this natural product. The synthetic strategy constructs the 14‐membered macrocyclic domain via Yamaguchi esterification followed by a challenging ring‐closing metathesis to effect the final formation of the macrolactone.